Willingness to communicte in english in different contexts among Chinese international university students in Malaysia - Ma, Huiling (2024)
The ultimate goal of English education is to cultivate students’English communication skills. However, researchers have observed that many learners of foreign and second languages, despite attaining high levels of fluency, often exhibit a reluctance to engage in communication in their target language. Consequently, willingness to communicate (WTC) in English has garnered significant attention from experts and scholars as a prerequisite for English communication behaviour. Existing research predominantly focuses on EFL learners either in English-speaking countries or their native EFL contexts, thereby neglecting willingness to communicate (WTC) practice and the contextual factors influencing WTC among the substantial number of international students studying in ESL countries. This study aims to provide a comprehensive understanding of the current practice of WTC in English among Chinese students studying in Malaysia, examining their L2 WTC experiences, perceptions of factors affecting their L2 WTC, and exploring the dynamics and outcomes of their WTC with different interlocutors across various conversational contexts. Employing a mixed research approach, the quantitative phase used a questionnaire survey to assess L2 WTC levels across multiple dimensions, reporting their WTC levels in various contexts (public, meetings, groups, dyads) and with different interlocutors (strangers, acquaintances, friends). The qualitative phase employed semi-structured interviews, focus group discussions, and focused essays to explore deeply the experiences and feelings of Chinese students regarding their WTC and to identify factors influencing their WTC. The results revealed that Chinese students studying in Malaysia demonstrated a moderate level of willingness to communicate (WTC) in English. Although their WTC level is not exceptionally strong, there is an overall positive tendency. Additionally, Chinese international students showed greater WTC in public and group contexts with friends and acquaintances. The study identified four categories of factors influencing participants’WTC in English: individual, social-cultural, educational, and environmental factors. Furthermore, this study recognized the dynamic nature of WTC in English, observing fluctuations based on interactions with different interlocutors across varied contexts. The study bears significant implications for L2 instructors, policymakers, and researchers. It is suggested that instructors could improve classroom efficiency by ensuring adequate preparation time, diverse group compositions, and discouraging sudden language switches. Policymakers can utilize insights from this study to formulate effective language education policies for Chinese students, including support programs for those with limited prior exposure to English. Future research could explore the dynamic nature of WTC across diverse social contexts and conduct comparative studies across countries and institutions to investigate the influence of language policies and cultural environments on students’communication attitudes.